ANALYSIS OF SEA WATER POLLUTION IN COASTAL MARINE DISTRICT TUBAN TO THE QUALITY STANDARDS OF SEA WATER WITH USING STORET METHOD - Perdana Ixbal Spanton; Abdul Aziz Saputra (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2017)
The sea water is a component that interacts with the terrestrial environment, where sewage from the land will lead to the sea. Waste containing these pollutants will enter into coastal waters and marine ecosystems. Partially soluble in water, partially sinks to the bottom and was concentrated sediment, and partly into the body tissues of marine organisms. This study was conducted to determine the level of pollution of sea water on the coast in the district of Tuban. This research was conducted in the Coastal Water Tuban, East Java. The main material used in research on Analysis of Water Pollution in Coastal Sea on Tuban. The method used in this research is using storet method and compared to the quality standards of the Environment Decree No. 51 in 2004. Based on the analysis of testing at five sampling point’s seawater around Bodies Tuban, obtained by sea water quality measurement results either in physics, chemistry, and microbiology varied. The level of pollution of sea water around Coastal Tuban obtained by using Storet Method average value of analysis is -4.2 included in class B are lightly blackened, while using values obtained Pollution Index average pollution index of 3.60 is included in the category lightly blackened. Keywords: Analysis of the pollution level of seawater on the coast in Tuban, Quality Standards of Sea Water, Storet Method.